On Markovian spectrum - Freiman, G. A.; Yudin, A. A. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Г. А. Фpейман, А. А. Юдин. О спектре МарковаG. A. Freimanas, A. A. Judinas. Apie Markovo spektrą